Teamwork competence: Definition and categorization - Torrelles, Cristina; Coiduras, Jordi; Isus, Sofía; Carrera, Xavier; París, Georgina; Cela, José M. (Profesorado, Revista de Currículum y Formación del Profesorado, 2011)
The competence of teamwork is imposed to the labor individualization. The change of structure and process of the organizations of the current society has generated a great impact in the new way of working. The tasks have increased its difficulty, doing that individual resolution is impossible. It is for this motive, that the organizations of the work claim, today more than never, the transversal competence of teamwork. This concept (Competence of Teamwork) recently new in the organizations offers definitions and underlying models of categorization who need to make be heard in the social and labor context. In this review of the literature there are analyzed the 4 most representative models of the competence, across which one proposes a definition of the competence and a possible structure of the categorization of it.